Heinrich Schliemann in Kazan: 'I went to the Kremlin to see one church there…' - E.A. Chiglintsev; N.I. Khanbekova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The journey of Heinrich Schliemann (1822–1890), the major Russian trader and world famous archaeologist, as well as the founder of Mycenology, along the Volga River with a visit to Kazan was discussed. It was his last travel before starting a career of ancient archaeologist. In the recent decades, H. Schliemann’s travelogues have been actively published and studied by historiographers. They disclose some details of his trading, personal life, and researcher skills. Among all other notes, the ones about his travel along the Volga River in 1866 are most important: he provided detailed descriptions of the expenses and the life of urban settlements. H. Schliemann considered the life conditions in cities along the Volga River as bad. At the same time, the sights of Nizhny Novgorod, Kazan, and Saratov attracted his attention. As a future archaeologist, H. Schliemann was interested landscapes, conditions of riverbanks, spring flood consequences, etc. H. Schlimann’s notes, about Kazan in particular, were compared with the newspaper publications and guidebooks of the period under study. Based on his vision, it was concluded that H. Schlimann’s interest in archaeology and Greek antiquities was clear during the Russian period of his life. H. Schliemann’s travel ended in the south of Russia, in areas related to the Hellenic civilization. His notes made in Taganrog are the observations of a future ancient archaeologist.